Knowledge of Fertile Period and Its Determinants Among Women of Childbearing age in Ethiopia: A Multilevel Analysis Based on 2016 Ethiopian Demographic and Health Survey - Wolde, Maereg; Kassie, Ayenew; Shitu, Kegnie; Azene, Zelalem Nigussie (Frontiers in Public Health, 2022)
Abstract Back ground: Knowledge of the fertile period is one of the science techniques used to delay pregnancy. Although it is highly effective method, most women lack correct knowledge about it and end up with unintended pregnancies and undergone through unsafe abortion, which is among the leading factor for maternal death. Therefore, this study is aimed to assess the knowledge about fertile period and its determinant factors among reproductive age women in Ethiopia. Methods: The data were extracted from the 2016 national cross-sectional Ethiopian Demographic and Health Survey. The data were collected using a two-stage cluster design. Descriptive statistics were used to summarize the study findings. The determinants of knowledge about fertile period were analyzed using a multilevel binary logistic regressions model. Results: A total of 15, 683 women were included. From this, 23.6% (95% CI: 23 - 24) had knowledge about fertile period. Age group 20-24 years, 25-29 years, 30-34years, 35-39 years, 40-44 years, 45-49 years, accomplishment of primary education, secondary education, and higher education, partner level of education, wealth index of poorer: middle, richer, and richest, listening to radio < once in a week, and watching Tv at least once in a week and who ever heard about family planning, internet usage in the last 12 months and community family planning message exposure were significantly associated with knowledge about fertile period. Conclusion: Reproductive age women who know about fertile period is low in Ethiopia. Age above 19 years, respondent’s having formal education, partner level of education, being poorer to richest wealth index, radio listening, watching Tv, ever heard FP, internet use and community family planning exposure were significantly associated with good knowledge about fertile period. Hence awareness rising about female fertile period for Ethiopian women of reproductive age is required with a due emphasis to adolescent, illiterate partner, illiterate respondent, protestant religion followers, internet non-users, poorest women and to those who are not exposed to tv, radio and family planning messages.